P140 Challenges in colonoscopic surveillance in chronic IBD. (25th January 2019) - Gillespie, S-L; Singh-Clark, N; Shand, A; Lees, C; Arnott, I; Ho, G-T; Watson, E; Noble, C; Din, S
Abstract: Background: Chronic inflammatory bowel disease (IBD) is associated with a 2- to 4-fold elevation of lifetime risk of colorectal cancer (CRC). Regular colonoscopic surveillance and the detection of colonic epithelial dysplasia are the gold standard for the early detection of CRC. Despite this, up to a third of patients will develop CRC within 3 years of a normal colonoscopy. We therefore aimed to calculate our post-colonoscopy CRC rate and identify the root causes for these cancers to inform where practice could be improved. Methods: Surveillance colonoscopy procedures were extracted from Unisoft® from April 2008 to December 2015 to allow determination of the 3-year post colonoscopy cancer rate. Results: 1460 procedures were undertaken including 845 males (58%) with a mean age of 53 years (range 17–88 years). The IBD diagnosis was: 1051 ulcerative colitis, 337 Crohn's disease and 72 IBD-Unclassified. Chromoendoscopy was adopted in 2012 and is achieved in approximately 50% of these procedures. Reasons for non-compliance with the use of chromoendoscopy include patient factors (poor bowel preparation, concurrent colonic inflammation and extensive pseudopolyposis), equipment factors (no dye spray) and endoscopist skill. Chromoendoscopy led to a significant reduction in the mean number of random colonic biopsies from 17 to 11 ( p < 0.05). The post-colonoscopy cancer rate was <10% in our unit. Low-grade dysplasia was not a robust marker of future CRC compared with high-grade dysplasia. Conclusions: We demonstrate the challenges in detecting CRC in patients with chronic IBD and confirm the poor clinical utility of low-grade dysplasia in predicting future CRC. There is an urgent need to develop more objective predictive biomarkers of future CRC risk.